Integrating payment for environmental services into an approach informed by the ecology of law: a case study on brazilian waste pickers - Gonçalves, Ana Paula Rengel (2021)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Jurídicas, Programa de Pós-Graduação em Direito, Florianópolis, 2021.